1996
DOI: 10.1021/ja955035r
|View full text |Cite
|
Sign up to set email alerts
|

Model Studies of the (6−4) Photoproduct DNA Photolyase:  Synthesis and Photosensitized Splitting of a Thymine−5,6-Oxetane J. Am. Chem. Soc. 1995, 117, 11375−11376

Abstract: Recent X-ray crystallographic and 1 H-NOE data indicate that the stereochemistry of 1 and 2 was incorrectly assigned. Both 1 and 2 as synthesized are in fact R-rather than -anomers. Compound 3 is correct as shown. The original assignments were made based on correlation with a published proton NMR spectrum of a related phenyl nucleoside, and also by correlation of H-1′ coupling constants to known R-and -nucleosides. It is now evident that these coupling patterns are generally reversed for aromatic C-deoxynucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A comparison of the current theoretical findings from BQ-Ox and NQ-Ox with those previously observed for head-to-head and heat-to-tail oxetane regioisomers composed of benzophenone and dimethylthymine (HH and HT, respectively) 21 shows that the state crossing (CP) occurs prior to the TS region and after the 3 BQ-Ox* diradical in BQ-Ox, NQ-Ox and HT, whereas it is located at the TS region for HH. This imposes an energetic barrier to reach the 3 EXC* structure in BQ-Ox, NQ-Ox and HT, which is not present in HH.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…A comparison of the current theoretical findings from BQ-Ox and NQ-Ox with those previously observed for head-to-head and heat-to-tail oxetane regioisomers composed of benzophenone and dimethylthymine (HH and HT, respectively) 21 shows that the state crossing (CP) occurs prior to the TS region and after the 3 BQ-Ox* diradical in BQ-Ox, NQ-Ox and HT, whereas it is located at the TS region for HH. This imposes an energetic barrier to reach the 3 EXC* structure in BQ-Ox, NQ-Ox and HT, which is not present in HH.…”
Section: Resultsmentioning
confidence: 64%
“…[13][14][15][16][17] In this regard, since the primary Thyh<iThy dimers are not isolable due to their chemical instability, 18 a variety of model oxetane conjugates composed of benzophenone (BP) and thymine (Thy) or uracil (Ura) derivatives have been employed in order to investigate the mechanism of photoinduced ring opening by means of spectroscopic techniques. [19][20][21][22][23] Although these models are far from the real Thyh<iThy dimers, the BP moiety has been found to be convenient to follow the course of the photoreaction by transient absorption spectroscopy, which allows rapid and quantitative detection of the BP triplet excited state ( 3 BP*), 24 amongst other transient species. Interestingly, irradiation of BP-Thy and/or BP-Ura oxetanes results in some cases in a rare ''adiabatic'' ring splitting process involving diradical species and triplet exciplexes, which ultimately evolve leading to the formation of 3 BP* and Thy (or Ura) in its ground state.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Ulteriorly, without the help of additional photosensitizers or enzymes, the direct photolysis of oxetane adducts formed by the BZP-photosensitized DNA damage and 6-4PPs damage is an effective and feasible approach. 14,26,27 The nanosecond timeresolved absorption studies observed that the photoinduced cycloreversion of oxetane adducts generated the triplet excited BZP along with ground state thymine. 28 The ultrafast timeresolved spectra indicated that the cycloreversion reaction occurred in a stepwise manner in a singlet excited state, and then ISC occurs to produce the triplet carbonyl product.…”
Section: Introductionmentioning
confidence: 99%